Emotional and social competencies and perceptions of the interpersonal environment of an organization as related to the engagement of IT professionals - Pittenger, Linda M. (Frontiers in Psychology, 2015)
There is a dearth of research focused on the engagement of information technology (IT) professionals. This study analyzed the relationship between emotional and social competencies and the quality of the IT professional’s perceptions of the interpersonal environment in an organization as they relate to employee engagement. Validated instruments were used and data was collected from 795 IT professionals in North America to quantitatively analyze the relationship between emotional and social competencies, role breadth self-efficacy (RBSE), with the quality of the IT professional’s perceptions of the interpersonal environment, and those perceptions with employee engagement. The study results indicate that specific emotional and social competencies and RBSE relate differently to the quality of the perceptions of the interpersonal environment. The study also reveals how the quality of the IT professional’s perceptions of the interpersonal environment relates to how much they engage in the organization. The findings indicate that the relationship between achievement orientation and the perceived interpersonal environment was positive and the relationship between influencing others and the perceived interpersonal environment was negative. Understanding such relationships offers much needed insight to practitioners and can benefit organizations that wish to increase the engagement of their IT professionals. The findings also can support practitioners to more effectively select and develop talent with the desired motives and traits. By doing so, organizations can experience increased employee satisfaction, engagement, and retention, resulting in higher productivity, quality, and profitability.